Design and Development of IDS for AVB/TSN - NASCIMENTO, Rodrigo Antônio Alves do (2019)
In the past few years, the number of attacks focusing on automotive systems have grown tremendously. In general, to combat such attacks, the use of a layered model of security is advised, where complementary security mechanisms can be applied to protect devices. Among them are Intrusion Detection System (IDS), which monitor systems to detect anomalous activities. With the emerging use of deterministic Ethernet brought by AVB/TSN into automotive Ethernet networks, newer attack surfaces are expected in cars. These are related to the set of new features to enable the parallel transmission of time-sensitive and best-effort media, management data, stream reservation, time synchronization and the connections among them. This thesis fills the gap left by previous works by: Summarizing exploitation vectors present on transport protocols (IEEE 1722/1733), management protocol (IEEE 1722.1) and time synchronization (IEEE 802.1AS); Dis-cussing the software/hardware requirements of the IDS, which also incorporates IEEE 802.1Qci features, deployed on an automotive switch present in a central gateway; Sharing the challenges of designing and implementing an IDS for AVB/TSN; Introducing IDS concepts for other TSN protocols such as 802.1CB and 802.1Qbu. To conclude the thesis, the results of a practical testbed using automotive equipment and testing tools used to confirm the feasibility of such a system will be shown. This evaluation measures whether the IDS, as an additional processing layer in the switch, impacts on the normal switch performance.